Are boards on board? A model of corporate board influence on sustainability - Galbreath, Jeremy (ANZAM, 2011)
A model is developed that takes into account: (1) human capital of outside directors; (2) social capital of outside directors; and (3) human and social capital of CEOs. Beyond this, values are largely neglected in the examination of boards of directors, and are also necessary in the study of sustainability given its normative implications. The model thus accounts for the value attunement concept as a moderating variable. The model proposed in this paper offers original insight into the drivers of sustainability performance in organisations and hence, advances corporate governance theory.